2007
DOI: 10.1007/bf02685932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead exposure on liver lipid peroxidative and antioxidant defense systems of protein-undernourished rats

Abstract: The effect of the liver mitogen, lead nitrate [Pb(NO3)2], on protein-undernutrition-induced increased lipid peroxidation and reduced antioxidants levels was investigated in rats. Animals were divided into four groups: A, B, C, and D of five animals each. Animals in groups C and D were placed on a low-protein diet (5% casein) and animals in groups A and B were maintained on a normal diet (16% casein) for 14 wk and fed ad libitum. Animals in groups B and D were each given a single intravenous injection of Pb(NO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…It has been shown to cause permanently reduced cognitive capacity (intelligence) in children, with apparently no lower threshold to the dose-response relationship (unlike other heavy metals such as mercury) [71]. This neurotoxicity was later found to be associated with lead-induced production of ROS which caused increase or decrease in the levels of lipid peroxidation or antioxidant defense mechanisms in the brain of experimental animals, and the effects were concentration dependent [7274]. …”
Section: Leadmentioning
confidence: 99%
“…It has been shown to cause permanently reduced cognitive capacity (intelligence) in children, with apparently no lower threshold to the dose-response relationship (unlike other heavy metals such as mercury) [71]. This neurotoxicity was later found to be associated with lead-induced production of ROS which caused increase or decrease in the levels of lipid peroxidation or antioxidant defense mechanisms in the brain of experimental animals, and the effects were concentration dependent [7274]. …”
Section: Leadmentioning
confidence: 99%
“…It can disturb cellular signaling and metabolism, ionic transportation, and enzyme activities by replacing mono- and bivalent cations [36]. In addition to its ionic activity, Pb triggers the generation of reactive oxygen species (ROS), which promotes oxidative damage to lipids, DNA, and proteins [37]. Accordingly, elevated LPO and NO was accompanied by a depletion of cellular antioxidants within the liver and kidneys of G. nanus , demonstrating an oxidative stress status.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that low dose of mercury could incur oxidative stress and hepatic damage. Besides mercury, lead was also found to exacerbate liver lipid peroxidation in protein-undernutrited rats, in which the study also suggested that free radicals is a pathological mechanism for hepatotoxicity of lead [ 59 ]. Microcystins are algae toxins produced by cyanobacteria, kind of cyclic nonribosomal peptides, possessing hepatotoxicity that may cause severe injury to the liver.…”
Section: Oxidative Stress In Liver Diseasesmentioning
confidence: 99%